Responses to extensive reading: a survey of ESL learners - Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Abdul Wahab, Nurshidah; Sarudin, Isarji; Abdullah, Aishah@Adeline Low Hui Lin; Md Daud, nuraihan (IIUM Press, 2011)
The fact that extensive reading positively contributes to language acquisition has been well documented and generally language instructors acknowledge the important role extensive reading plays in the acquisition of a second language. However, very few language curricular around the world integrate extensive reading as part of a student's langauge learning syllabus due to a number of constraints. This study reports on feedback from 2,471 learners studying English as a second language in an intensive pre-university programme where graded readers were used as part of the extensive reading programme. Among others, this research highlights learners' responses towards the extensive reading programme and the problems they experienced. Pedagogical implications for the success of an extensive reading programme were also discussed.